Models of internet connectivity for secondary schools in the Grahamstown circuit - Brandt, Ingrid Gisélle (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
Information and Communication Technologies (ICTs) are becoming more pervasive in South African schools and are increasingly considered valuable tools in education, promoting the development of higher cognitive processes and allowing teachers and learners access to a plethora of information. This study investigates models of Internet connectivity for secondary schools in the Grahamstown Circuit. The various networking technologies currently available to South African schools, or likely to become available to South African schools in the future, are described along with the telecommunications legislation which governs their use in South Africa. Furthermore, current ICT in education projects taking place in South Africa are described together with current ICT in education policy in South Africa. This information forms the backdrop of a detailed schools survey that was conducted at all the 13 secondary schools in the Grahamstown Circuit and enriched with experimental work in the provision of metropolitan network links to selected schools, mostly via Wi-Fi. The result of the investigation is the proposal of a Grahamstown Circuit Metropolitan Education Network.
Keywords: Internet in education -- South Africa -- Grahamstown; Computer networks -- South Africa -- Grahamstown; Information technology -- Study and teaching (Secondary) -- South Africa -- Grahamstown; Information technology -- South Africa -- Grahamstown; Computer-assisted instruction -- South Africa -- Grahamstown; Telecommunication in education -- South Africa -- Grahamstown; Education, Secondary -- South Africa -- Grahamstown -- Data processing